Does Repeated Ticking Maintain Tic Behavior? An Experimental Study of Eye Blinking in Healthy Individuals. (8th May 2014) - Beetsma, Daniel J. V.; van den Hout, Marcel A.; Engelhard, Iris M.; Rijkeboer, Marleen M.; Cath, Danielle C.
Abstract : Tics in Tourette syndrome (TS) are often preceded by "premonitory urges": annoying feelings or bodily sensations. We hypothesized that, by reducing annoyance of premonitory urges, tic behaviour may be reinforced. In a 2 × 2 experimental design in healthy participants, we studied the effects of premonitory urges (operationalized as air puffs on the eye) and tic behaviour (deliberate eye blinking after a puff or a sound) on changes in subjective evaluation of air puffs and EMG responses on the m. orbicularis oculi. The experimental group with air puffs + blinking experienced a decrease in subjective annoyance of the air puff, but habituation of the EMG response was blocked and length of EMG response increased. In the control groups (air puffs without instruction to blink, no air puffs), these effects were absent. When extrapolating to the situation in TS patients, these findings suggest that performance of tics is reinforced by reducing the subjective annoyance of premonitory urges, while simultaneously preventing habituation or even inducing sensitisation of the physiological motor response.